On controlled Hamilton and Hamilton–Jacobi differential equations of higher-order - Savin Treanţă; Kamsing Nonlaopon; Muhammad Bilal Khan (Scientific Reports, 2022)
Abstract In this paper, we investigate the nonlinear dynamics associated with controlled Lagrangians involving higher-order derivatives. More precisely, we establish the controlled higher-order Hamilton ordinary differential equations (ODEs) and Hamilton–Jacobi partial differential equation (PDE) for the considered class of Lagrangians governed by higher-order derivatives of the state variables. Moreover, we formulate and prove an invariance result with respect to the state variable. In addition, in order to validate the theoretical results and to highlight their effectiveness, some illustrative applications are presented.